CRIMINAL LAW ENFORCEMENT AGAINST PERPETRATORS OF FOREST FIRES FOR AGRICULTURAL LAND CLEARING IN INDONESIA - Febiyansastin, Wayu (Communale Journal, 2025)
Abstract: : Land clearing that leads to forest fires constitutes a serious threat with far-reaching impacts on the environment, public health, and the national economy. Forest fires contribute to biodiversity loss, air pollution, climate change, and significant social and economic losses, particularly for communities living near affected areas. This research examines the regulatory framework and the implementation of law enforcement in Indonesia concerning perpetrators of land clearing activities that result in forest fires. It also analyzes the role of the government in preventing and controlling forest fires, as well as the obstacles encountered in the enforcement process. The study employs a case approach combined with a normative juridical method, relying on the analysis of relevant laws, regulations, court decisions, and legal literature. The results of the study indicate that perpetrators of land clearing causing forest fires may be subject to legal sanctions, including criminal penalties such as imprisonment and fines, as well as administrative and civil liability. Furthermore, the government plays a crucial role in forest fire prevention and suppression through policy formulation, supervision, and coordination among institutions. However, law enforcement faces several obstacles, including weak supervision, limited resources, difficulties in evidence collection, and lack of compliance by corporations and local actors.